Perhitungan Jumlah Kendaraan Bermotor Di Kecamatan Mandau dengan Menggunakan Metode Traffic Counting - Fatatulkhairani Fatatulkhairani; Aryo Sasmita; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Mandau Sub-district is one of the regions that has considerable transportation activities in Riau Province. Therefore, the calculation of the total of vehicles is very necessary to find out the total of vehicles that passed through the roads in Mandau Sub-district. This research was conducted to determine the total of motorized vehicles produced during peak hours on Mondays. The method of this study was recording the traffic activity to count the total of motorized vehicles that passed through the road in Mandau Sub-district. The results of this study were the total of motorized vehicles during peak hours on Monday for each road was 9,070 units on Hangtuah Street, 7,581 units on Mawar Street, and 2,442 units on Pertanian Street. This showed the magnitude of transportation activities in Mandau Sub-district. Keyword: Mandau Sub-district, Transportation, and Traffic Counting.